Osmanlı arşiv belgelerine göre işgal döneminde İstanbul (13 kasım 1918-15 mart 1920) - Şahin, Şeyma (My University, 2009)
SARISU DERESİ VE KARADENİZE BİRLEŞME NOKTASINDA MİKROBİYOLOJİK VE KİMYASAL KİRLİLİK SEVİYESİNİN TESPİTİ Bu çalışmada Sarısu deresi ve dereyi besleyen kollarla Karadenize birleşme noktasındaki kirletici etmenler araştırılmıştır. Bu çalışmanın amacı Sarısu deresindeki kirliliği saptamak ve kirlilik kaynağı oluşturan etmenlerin tespitini sağlamaktır. Haziran 2007 –Mayıs 2008 tarihleri arasında seçilen 9 ayrı noktadan her ay periyodik olarak, toplam 144 su örneği alınıp bakteriyolojik ve kimyasal analizler yapılmıştır. Laboratuvar çalışmaları Marmara Üniversitesi Doğa Bitkileri ve Su Ürünleri Araştırma ve Uygulama Merkezi laboratuvarında gerçekleştirilmiştir. Bakteriyolojik araştırmalar için numuneler bir yıl boyunca her ay alınmıştır. Çalışmada numune alım noktalarındaki Toplam Koliform değerleri saptanmıştır. Toplam Koliform bakteri sayısı “Membran Filtrasyon Tekniği” kullanılarak saptanmıştır. Kimyasal kirliliği tespit etmek için Kurşun, Kadmiyum, Alüminyum, Toplam Demir, Deterjan, Nitrit, Nitrat, Fosfor, Fosfat Amonyak ve Organik Madde parametreleri ile ayrıca Kimyasal Oksijen İhtiyacı, Biyolojik Oksijen İhtiyacı, Toplam Çözünmüş Katı Madde, İletkenlik, Renk, Bulanıklık, pH ve Sıcaklık parametrelerinin analizleri yapılmıştır. Araştırma neticesinde elde edilen değerler, Amerikan Çevre Koruma Ajansı ve T.C. Başbakanlık ve Çevre Müsteşarlığınca hazırlanan Su Kirlilik Kontrol Yönetmeliği içinde yer alan Kıtaiçi Su Kaynaklarının Sınıflarına Göre Kalite Kriterleri standartlarıyla karşılaştırılmıştır. Sonuç olarak Sarısu deresinde ciddi bir organik madde ve Toplam Koliforma göre mikrobiyolojik kirlilik saptanmıştır. Ayrıca Amonyak, Nitrit, Fosfor ve Fosfat parametreleri kabul edilebilir değerlerin oldukça üstündedir. Bu durumuyla derede bazı canlılar için uygun olmayan yaşam koşullarının oluştuğu saptanmıştır.

This research is about searching of the de facto occupation’s period of İstanbul through the medium of the Ottoman archive documents in the days that followed the Mondros Armistice. Before İstanbul was occupied officially by the Allies,the native of İstanbul were under bad circumstances. The Allies were behaving as if they had already occupied the city. This period lasted one year, four months and three days. These difficulties and desperations brought about appearing the idea of national struggle and searching a new leader. In that time, Atatürk was in İstanbul. He tried to find some solutions to prevent the Allies from occupying of İstanbul. He stayed in İstanbul for six months. When he realized that he could have done nothing in this city under the occupation, he went to Anatolia and started the national struggle there. Official occupation of İstanbul began on November 13, 1918 and ended on March15, 1920. This occupation period caused many different terrible situations and applications. We understand that the Ottoman government and people were under pressure and in difficulty when we inspect the Ottoman archive documents. But the pressure non muslim groups had done by trusting the Allies was much more. In this matter the İstanbul Greek were the first group, second group was Armenian and the last group was Jews. At the same time, the İstanbul Greek were the most supported group by the Allies. The Patriatic and church had an active part in this event. The Ottoman archive documents show that they had moved heaven and earth to be given İstanbul back to themselves .They formed hidden associations, joined international assemblies and used press in order to get İstanbul We understand that The Ottoman government knew not only political activities but also military activities but they weren’t able to interfere. English stood out with the occupation. The allies let the non muslim prisoners go in the prison without noticing their offences. However, English were more active than the others. The Allies created their own prisons. They inflicted Turks and muslims committing crimes against themselves. They judged their own soldiers who committed offence in their law courts, too. There were so many the Allies’ soldiers committing simple offences. French and Greek soldiers were more effective ones. The Allies kept down the native of İstanbul. They were on a razor. Breaking houses, malicious injury, theft, insulting to Turks and muslims were some of these bad events. When people sometimes rebelled, the Allies chastised them immediately. In many events against themselves, the Allies judged and punished the İstanbul without consulting with the Ottoman government or Sultan. At first, Sultan knew the time of the day and caught out the occupation since he had believed English Goverment‘s unwritten agreement too much. The Allies imposed and acted in their own initiatives. They colonized Istanbul using his great confusion.
Keywords: İstanbul (Türkiye)_Tarih; İstanbul’un İşgali